A physical and semi-analytical comparison between coaxial BHE designs considering various piping materials. (15th December 2017) - Gordon, David; Bolisetti, Tirupati; Ting, David S-K.; Reitsma, Stanley
Abstract: This paper presents an improved semi-analytical model for the heat transfer related to a coaxial borehole heat exchanger (BHE). This model, referred to as the composite coaxial (CCx) model, is verified using results from three different thermal response tests performed on full-scale coaxial BHEs having various pipe size and material properties. The model is further used to analyze the performance and length requirements of various coaxial configurations comparing the use of a steel outer pipe to an insulated inner pipe. This comparison is made considering standard HDPE pipe sizes as the status quo, where the parameters are kept within the verified tested limit of the model. The results show, in comparison to using an insulated inner pipe, that a steel outer pipe has a greater impact on reducing the overall length requirement while maintaining system performance. Highlights: Proposes a thermal presence ratio within the composite coaxial model. Extends composite coaxial model validation using additional thermal response tests. Adapts the composite coaxial model for the purpose of case-by-case design. A steel outer pipe is found to be more beneficial than an insulated inner pipe.